EFFECT OF DIFFERENT ROOF HOUSE ON PHYSIOLOGICAL AND BLOOD PARAMETERS OF SWAMP BUFFALO CALVES OF ASSAM* (Indian Journal of Animal Production and Management, 2014)
In the present investigation, the physiological and blood parameters of swamp buffalo calves of similar age and average body weight of Assam housed under different roof coverings were studied. The calves were randomly allocated to Treatment 1 (T1), 2 (T2) and 3 (T3) with asbestos roof, asbestos roof with bamboo ceiling, and thatch roof house respectively. The calves were provided with ad libitum chaffed green forages like Maize, Napier, Para, and Cowpea along with concentrate mixture at the rate of 0.5 per cent of their bodyweight. The overall mean respiration rate and pulse rate of calves were recorded to be 21.07 ± 0.13, 20.95 ± 0.17 and 20.89 ± 0.16; 60.61 ± 0.10, 60.37 ± 0.10 and 60.38 ± 0.11 per minute in T1, T2 and T3 groups respectively. The overall mean rectal temperature was found to range from 38.2°C to 38.3°C. The overall blood glucose level was recorded as 72.61 ± 2.11, 72.22 ± 2.17 and 74.21 ± 2.35 mg/dl in T1, T2 and T3 groups respectively. No significant difference was observed in the above parameters among the three groups. No significant difference was also observed in total serum protein, sodium, potassium, and haemoglobin levels among the groups. The thatch was observed to be the better roof material to create beneficial microenvironment around the buffalo calves by reducing thermal stress.
Keywords: Swamp buffalo; physiological and blood parameters; different roof coverings